Multiple Faceted Roles of Cocaine in Potentiation of HAND - Cai, Yu; Yang, Lu; Callen, Shannon; Buch, Shilpa (Current HIV Research, 2016)
Background: While the advancement of highly active antiretroviral therapy (HAART) has transformed the course of HIV/AIDS from a death sentence to a manageable chronic condition, the prevalence of a constellation of neurological disorders collectively termed as HIV-associated neurocognitive disorders (HAND) continues to persist in these patients. HAND is characterized by cognitive dysfunction, depression, impaired memory and/or deficits in motor skills. The underlying factors leading to HAND have been the subject of extensive research and are thought to be associated with HIV infection in the CNS combined with robust immune activation of resident cells of the CNS. In addition, there is a strong correlation between chronic substance abuse and the manifestation of HAND. Among the various commonly abused drugs, cocaine has been extensively studied for its ability to exacerbate the neuropathogenesis of HAND. Ample evidence suggests that cocaine not only facilitates viral replication in macrophages and microglia, but also inflicts deleterious effects on various other cells of the CNS, thereby contributing to the potentiation of HAND. Cocaine has been shown to enhance the permeability of the blood-brain barrier (BBB) through various mechanisms including direct pro-apoptotic effects on brain endothelial cells, systemic induction of inflammatory factors which have been demonstrated to down-regulate tight junction proteins and via up-regulation of several endothelial adhesion molecules leading to accelerated breach of the BBB and increased influx of HIV-infected leukocytes into the CNS. Cocaine also enhances viral replication in CNS astrocytes and promotes astrogliosis via astrocyte activation and proliferation. Furthermore, cocaine also exacerbates neuroinflammatory responses by mediating microglial activation and migration. In addition to cellular injury mediated by inflammatory responses, cocaine also directly affects the brain reward system by disrupting the homeostasis of neurotransmitters such as dopamine and acetylcholine and works synergistically with viral proteins such as tat and gp120 to promote neuronal injury. Conclusion: This review highlights previous studies in the field on the role of cocaine in the progression of HAND and gives an overview of the major signaling pathways in the CNS that are involved in this process.
Keywords: neurons